Incentives of retirement transition for elderly workers: An analysis of actual and simulated replacement rates in Ireland - Jinjing Li; Cathal O'Donoghue (Institute for the Study of Labor (IZA), 2011)
Retirement behaviours and elderly poverty issues have been the subject of much attention and discussion in recent years as most countries are facing a rapidly ageing society. Ireland enjoys a relatively young population compared with other European countries, but is also struggling with increasing fiscal pressures. This paper analyses the retirement pattern and the replacement rate observed in Ireland using the Living in Ireland panel dataset. Since traditional empirical estimations may have selection bias issues as people with low replacement rates may not choose to retire, the paper adopts a combined method with both synthetic household simulation and empirical estimates. The study reveals the social economic attributes patterns associated with the replacement rates and retirement behaviours, and explores the heterogeneities of replacement rates among retirees.
urn:nbn:de:101:1-201108092920
Keywords: J14; 330; retirement; replacement rates; microsimulation